Turkey's state crisis - Aras, Bülent, 1971- (Syracuse, New York)
xii, 146, [1] sayfa
Keywords: “What accounts for the regression of Turkey's stature from a “model“ country to one riddled with state crisis and conflict? Unable to adapt to the challenges of the era and failing to respond to ethnic and multicultural political demands for reform, the Turkish state has resisted change and stuck to its ideological roots stemming from the 1930s. In Turkey's State Crisis, Aras delves into the historical, political, and geopolitical background of the country's decline. In an effort to delineate the origin of the crisis, Aras investigates several perspectives: the political elites' attempt to change the administrative system to create a performance-oriented one; the bureaucracy's response, concerns, and resistance to change; the state's conflict resolution capacity; and the transformation of foreign/security policy. Providing a comprehensive portrait of the Turkish state's turmoil, Aras creates a blueprint for the ways in which much-needed reforms can break vicious cycles of political polarization, rising authoritarianism, and weak state institutions.” --